Pengoptimalan Moderasi Beragama Melalui Media Interaktif Berbasis Nearpod Di Madrasah Ibtidaiyah - Yulia, Nurul Mahruzah; Adistya, Ananda Feby; Amreta, Midya Yuli (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The purpose of this study is to describe the process and results of developing interactive media based on Nearpod on the material of religious diversity in Indonesia. The ADDIE model was chosen in Research and Development (R&D). This development model consists of five steps, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The results of the study indicate that interactive media based on Nearpod is very feasible and can be used for learning with a validity level of 80% from media experts, 90% from material experts, 82% from learning experts, and student responses of 79% (very good and acceptable). The effectiveness of interactive media based on Nearpod is shown by an increase in attitudes and abilities of religious moderation with an N-Gain value of 0.62 in the moderate category. The significance of this study lies in its contribution to providing effective learning tools to improve attitudes of religious tolerance among students, which can help build a more harmonious and tolerant society.